An extended root phenotype: the rhizosphere, its formation and impacts on plant fitness. (23rd May 2020) - de la Fuente Cantó, Carla; Simonin, Marie; King, Eoghan; Moulin, Lionel; Bennett, Malcolm J.; Castrillo, Gabriel; Laplaze, Laurent
SUMMARY: Plants forage soil for water and nutrients, whose distribution is patchy and often dynamic. To improve their foraging activities, plants have evolved mechanisms to modify the physicochemical properties and microbial communities of the rhizosphere, i.e. the soil compartment under the influence of the roots. This dynamic interplay in root−soil−microbiome interactions creates emerging properties that impact plant nutrition and health. As a consequence, the rhizosphere can be considered an extended root phenotype, a manifestation of the effects of plant genes on their environment inside and/or outside of the organism. Here, we review current understanding of how plants shape the rhizosphere and the benefits it confers to plant fitness. We discuss future research challenges and how applying their solutions in crops will enable us to harvest the benefits of the extended root phenotype. Significance Statement: Plants have evolved mechanisms to modify the physicochemical properties and microbial communities of the rhizosphere. Here, we review our current knowledge on how plants create this extended phenotype through root−soil−microbiome interactions and the benefits it confers to plant fitness.